Biomedical magnesium alloy and preparation method thereof

CN119640368APending Publication Date: 2025-03-18SOLOMON (CHANGZHOU) ALLOY NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411941216.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Magnesium alloys rapidly degrade and corrode in a body fluid environment, resulting in hydrogen release, local alkalization and degradation of the mechanical properties of the implant, which in turn leads to premature failure of the implant.

Method used

By forming a microarc oxide film layer on the surface of the magnesium alloy matrix and preparing a polylactic acid-hydroxyapatite composite coating on its surface, the corrosion resistance and degradation stability of the magnesium alloy are enhanced.

Benefits of technology

It effectively delays the degradation rate of magnesium alloy, improves its corrosion resistance and stability in the body, reduces the risk of local alkalization, and extends the service life of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640368A_ABST
    Figure CN119640368A_ABST
Patent Text Reader

Abstract

The invention discloses a biomedical magnesium alloy and a preparation method thereof, and belongs to the technical field of magnesium alloy materials. The biomedical magnesium alloy comprises a magnesium alloy matrix, a micro-arc oxidation film layer is arranged on the surface of the magnesium alloy matrix, and a PLGA-HA composite coating is arranged on the surface of the micro-arc oxidation film layer. The micro-arc oxidation film serves as a magnesium alloy surface modification base layer, provides a good adhesion interface for the composite coating and enhances the corrosion resistance of a base body. By introducing the PLGA-HA composite coating on the micro-arc oxidation film on the surface of the magnesium alloy, the PLGA coats and stabilizes HA particles, so that the HA particles are distributed more uniformly, meanwhile, the bonding strength of the HA and the micro-arc oxidation film is improved, the stripping phenomenon of the coating is reduced, and the long-term stability of the coating is ensured. In addition, the composite coating further fills up pores and cracks of the micro-arc oxidation film, and the overall compactness and corrosion resistance are remarkably improved, so that the degradation rate of the magnesium alloy is effectively delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to a biomedical magnesium alloy and a preparation method thereof. Background Art

[0002] As a new generation of medical implant materials, magnesium alloys have attracted widespread attention for their excellent performance. First, magnesium alloys have good biocompatibility and will not cause immune rejection or adverse reactions. Secondly, magnesium alloys also have certain biological activity and can interact with human tissues to promote tissue repair and regeneration. In addition, magnesium alloys have excellent mechanical compatibility, and their mechanical properties are closer to human bones. Compared with traditional metal implants, they can better meet the human body's needs for implant mechanical properties. More importantly, magnesium alloys have degradability that other metal-based biomaterials do not have. They can be gradually degraded and absorbed in the human body, thereby avoiding the risk of traditional metal implants requiring secondary surgery to remove, greatly reducing the medical burden on patients.

[0003] However, magnesium alloys also face some challenges as medical implant material: due to their high chemical activity, they will degrade rapidly in the body fluid environment, which will lead to the release of hydrogen, local alkalization and a decrease in the mechanical properties of the implant, thus causing premature failure of the implant.

[0004] Therefore, solving the problem of rapid degradation and corrosion of magnesium alloys in body fluid environment has become an important research direction of magnesium alloy medical implant devices.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a biomedical magnesium alloy and a preparation method thereof, so as to solve or improve the above technical problems.

[0007] The present invention can be implemented like this:

[0008] In a first aspect, the present invention provides a biomedical magnesium alloy, which includes a magnesium alloy substrate, a surface of the magnesium alloy substrate having a micro-arc oxidation film layer, and a surface of the micro-arc oxidation film layer is provided with a polylactic acid glycolic acid-hydroxyapatite composite coating.

[0009] In an optional embodiment, the thickness of the micro-arc oxidation film layer is 5 μm to 10 μm;

[0010] And / or, the thickness of the polylactic acid-glycolic acid-hydroxyapatite composite coating is 20 μm to 30 μm.

[0011] In a second aspect, the present invention provides a method for preparing a biomedical magnesium alloy as described in the aforementioned embodiment, comprising the following steps: performing micro-arc oxidation treatment on a magnesium alloy substrate to form a micro-arc oxidation film on the surface of the magnesium alloy substrate; and preparing a polylactic acid-hydroxyapatite composite coating on the surface of the micro-arc oxidation film.

[0012] In an optional embodiment, the micro-arc oxidation treatment includes: connecting the magnesium alloy substrate to a power source via a wire and performing electrical oxidation in an electrolyte.

[0013] In an alternative embodiment, the electrolyte comprises an alkali metal, an inorganic salt, an organic additive and water;

[0014] The concentration of the alkali metal contained in the electrolyte is 10 g / L to 15 g / L, the concentration of the inorganic salt contained in the electrolyte is 5 g / L to 15 g / L, and the concentration of the organic additive contained in the electrolyte is 1 g / L to 10 g / L.

[0015] In an alternative embodiment, the alkali metal comprises at least one of KOH and NaOH.

[0016] In an alternative embodiment, the inorganic salt comprises at least one of Na2SiO3 and Na3PO4.

[0017] In an optional embodiment, the organic additive includes at least one of EDTA-2Na and glycerol; wherein, when the organic additive contains EDTA-2Na, the concentration of EDTA-2Na in the electrolyte is 1g / L to 3g / L; when the organic additive contains glycerol, the concentration of glycerol in the electrolyte is 1g / L to 10g / L.

[0018] In an optional embodiment, the voltage of the micro-arc oxidation treatment is 250V to 500V, the frequency of the micro-arc oxidation is 500Hz to 1500Hz, the duty cycle of the micro-arc oxidation is 5% to 10%, and the oxidation time of the micro-arc oxidation is 5min to 15min.

[0019] In an optional embodiment, before the micro-arc oxidation treatment, the magnesium alloy substrate is further subjected to surface pretreatment;

[0020] And / or, before preparing the polylactic acid-glycolic acid-hydroxyapatite composite coating, the method further includes cleaning the micro-arc oxidation film layer.

[0021] In an optional embodiment, preparing the polylactic acid-glycolic acid-hydroxyapatite composite coating includes: immersing a magnesium alloy substrate having a micro-arc oxidation film layer in a mixed solution of polylactic acid-glycolic acid and hydroxyapatite, followed by vertical pulling and drying to form a polylactic acid-glycolic acid-hydroxyapatite composite coating on the surface of the micro-arc oxidation film layer.

[0022] In an optional embodiment, the mixed solution includes a polymer solution formed by polylactic acid glycolic acid and a solvent and hydroxyapatite; wherein the solid-liquid ratio of polylactic acid glycolic acid to the solvent is 5g:100mL to 10g:100mL; the mass ratio of hydroxyapatite to the polymer solution is 5:100 to 20:100;

[0023] And / or, the copolymerization ratio of polylactic acid to polyglycolic acid is 50:50 to 85:15.

[0024] In an optional embodiment, the vertical pulling speed is 0.5 m / s to 3 m / s;

[0025] And / or, drying is performed at 35° C. to 45° C. for 6 h to 12 h.

[0026] The beneficial effects of the present invention include:

[0027] The present invention uses the micro-arc oxidation film as the surface modification base layer of the magnesium alloy, provides a good adhesion interface for the composite coating, and enhances the corrosion resistance of the magnesium alloy substrate. By introducing the PLGA-HA composite coating on the micro-arc oxidation film on the surface of the magnesium alloy, PLGA coats and stabilizes the HA particles, making their distribution more uniform, while improving the bonding strength between HA and the micro-arc oxidation film, reducing the peeling phenomenon of the coating, and ensuring the long-term stability of the coating. In addition, the composite coating further fills the pores and cracks of the micro-arc oxidation film, significantly improving the overall density and corrosion resistance, thereby effectively delaying the degradation rate of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 This is a graph showing the change in pH value of simulated body fluid (SBF) when each biomedical magnesium alloy is immersed in simulated body fluid (SBF) for different days in Experimental Example 1;

[0030] Figure 2 The potentiodynamic polarization curves of each biomedical magnesium alloy in Experimental Example 2 after being immersed in simulated body fluid (SBF) for 1 day;

[0031] Figure 3 The potentiodynamic polarization curves of each biomedical magnesium alloy in Experimental Example 2 after being immersed in simulated body fluid (SBF) for 15 days;

[0032] Figure 4 The potentiodynamic polarization curves of the biomedical magnesium alloys in Experimental Example 2 after being immersed in simulated body fluid (SBF) for 30 days are shown. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] The biomedical magnesium alloy and the preparation method thereof provided by the present invention are described in detail below.

[0035] The invention provides a biomedical magnesium alloy, which comprises a magnesium alloy substrate, a surface of the magnesium alloy substrate having a micro-arc oxidation film layer, and a surface of the micro-arc oxidation film layer is provided with a polylactic acid glycolic acid-hydroxyapatite composite coating (abbreviated as PLGA-HA composite coating).

[0036] Among them, the micro-arc oxidation film serves as the surface modification base layer of the magnesium alloy, providing a good adhesion interface for the composite coating and enhancing the corrosion resistance of the magnesium alloy substrate. By introducing the PLGA-HA composite coating on the micro-arc oxidation film on the surface of the magnesium alloy, PLGA encapsulates and stabilizes the HA particles, making their distribution more uniform, while improving the bonding strength between HA and the micro-arc oxidation film, reducing the peeling phenomenon of the coating, and ensuring the long-term stability of the coating. In addition, the composite coating further fills the pores and cracks of the micro-arc oxidation film, significantly improving the overall density and corrosion resistance, thereby effectively delaying the degradation rate of the magnesium alloy.

[0037] In some optional embodiments, the thickness of the micro-arc oxidation film layer can be 5μm to 10μm, such as 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, etc., or other values ​​within the range of 5μm to 10μm.

[0038] If the thickness of the micro-arc oxidation film is less than 5 μm, the thickness of the dense layer of the micro-arc oxidation film is too low, which is not conducive to the protection of the substrate; if the thickness of the micro-arc oxidation film is greater than 10 μm, the loose porous layer outside the micro-arc oxidation film will gradually increase, which is not conducive to the bonding strength between the micro-arc oxidation film and the polylactic acid-hydroxyapatite composite coating, resulting in a decrease in the overall mechanical properties of the coating.

[0039] In some optional embodiments, the thickness of the polylactic acid-glycolic acid-hydroxyapatite composite coating can be 20μm to 30μm, such as 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm or 30μm, etc., or it can be other values ​​within the range of 20μm to 30μm.

[0040] If the thickness of the polylactic acid-hydroxyacetic acid-hydroxyapatite composite coating is less than 20 μm, there may be local weak areas in the coating, resulting in the penetration of corrosive media, which is not conducive to the corrosion resistance of the alloy; if the thickness of the polylactic acid-hydroxyacetic acid-hydroxyapatite composite coating is greater than 30 μm, the coating is too thick and a large amount of lactic acid will be produced during the degradation process, resulting in a significant decrease in local pH, which is not conducive to maintaining pH balance.

[0041] Accordingly, the present invention provides a method for preparing the above-mentioned biomedical magnesium alloy, comprising the following steps: performing micro-arc oxidation treatment on a magnesium alloy substrate to form a micro-arc oxidation film on the surface of the magnesium alloy substrate; and preparing a polylactic acid-hydroxyapatite composite coating on the surface of the micro-arc oxidation film.

[0042] In some optional embodiments, before the micro-arc oxidation treatment, the magnesium alloy substrate is further subjected to surface pretreatment.

[0043] Exemplarily, the surface pretreatment includes: grinding the magnesium alloy substrate with 400#, 800#, 1500# and 2000# sandpaper in sequence until the surface is smooth without obvious scratches. Then, the ground magnesium alloy substrate is placed in an ultrasonic cleaner and cleaned with deionized water for 5min to 10min to remove surface dirt, and a hole is drilled on the back of the magnesium alloy substrate for a wire (such as an aluminum wire) to pass through and connect to a subsequent micro-arc oxidation power source.

[0044] In some optional embodiments, the micro-arc oxidation treatment includes: connecting the magnesium alloy substrate to a power source via a wire and performing electrical oxidation in an electrolyte.

[0045] The electrolyte includes alkali metal, inorganic salt, organic additive and water. The alkali metal is used to adjust the pH value of the electrolyte and increase the generation rate of the micro-arc oxidation film. The inorganic salt is used to enhance the wear resistance and hardness of the micro-arc oxidation film. The organic additive is used to increase the solubility of metal ions and thus improve the uniformity of the micro-arc oxidation film.

[0046] Among them, the concentration of alkali metal contained in the electrolyte can be 10g / L to 15g / L, such as 10g / L, 10.5g / L, 11g / L, 11.5g / L, 12g / L, 12.5g / L, 13g / L, 13.5g / L, 14g / L, 14.5g / L or 15g / L, etc., or it can be other values ​​within the range of 10g / L to 15g / L.

[0047] If the concentration of alkali metals in the electrolyte is less than 10g / L, the conductivity of the electrolyte will decrease, which may lead to uneven discharge and insufficient density and thickness of the micro-arc oxidation film, which is not conducive to film formation. If the concentration of alkali metals in the electrolyte is greater than 15g / L, the conductivity of the electrolyte is too high, which may lead to excessive discharge intensity and excessive film growth rate, which may easily cause peeling and cracking, and is not conducive to the stability of the film structure.

[0048] The concentration of the inorganic salt contained in the electrolyte can be 5g / L to 15g / L, such as 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L or 15g / L, or it can be other values ​​within the range of 5g / L to 15g / L.

[0049] If the concentration of inorganic salts in the electrolyte is less than 5g / L, the conductivity of the electrolyte decreases, and the ceramic phase in the film layer is not easy to form, which is not conducive to improving the hardness and wear resistance of the micro-arc oxidation film; if the concentration of inorganic salts in the electrolyte is greater than 15g / L, excessive salt deposition in the film layer is not conducive to the corrosion resistance and structural stability of the film layer.

[0050] The concentration of the organic additive contained in the electrolyte can be 1g / L to 10g / L, such as 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L or 10g / L, etc., or it can be other values ​​within the range of 1g / L to 10g / L.

[0051] If the concentration of organic additives in the electrolyte is less than 1g / L, the film formation rate will decrease, which is not conducive to the formation of a dense oxide layer; if the concentration of organic additives in the electrolyte is greater than 10g / L, the conductivity of the electrolyte will be affected, causing abnormal discharge, which is not conducive to film formation.

[0052] In some optional embodiments, the alkali metal may include at least one of KOH and NaOH. The inorganic salt may include at least one of Na2SiO3 and Na3PO4. The organic additive may include at least one of EDTA-2Na and glycerol.

[0053] When the organic additive contains EDTA-2Na, the concentration of EDTA-2Na in the electrolyte can be 1g / L to 3g / L, such as 1g / L, 1.5g / L, 2g / L, 2.5g / L or 3g / L, etc. When the organic additive contains glycerol, the concentration of glycerol in the electrolyte is 1g / L to 10g / L, such as 1g / L, 2g / L, 4g / L, 6g / L, 8g / L or 10g / L, etc.

[0054] In some optional embodiments, the voltage of the micro-arc oxidation treatment can be 250V to 500V, such as 250V, 300V, 350V, 400V, 450V or 500V, or other values ​​within the range of 250V to 500V. The higher the voltage, the greater the discharge energy, the faster the growth rate of the oxide film, the thicker the film, and the higher the porosity and roughness. In the specific operation, the constant voltage mode is maintained.

[0055] The frequency of micro-arc oxidation can be 500 Hz to 1500 Hz, such as 500 Hz, 800 Hz, 1000 Hz, 1200 Hz or 1500 Hz, or other values ​​within the range of 500 Hz to 1500 Hz. The above frequency range is conducive to forming a uniform and dense micro-arc oxidation film; if the frequency is too high, the discharge energy will be reduced.

[0056] The duty cycle of micro-arc oxidation can be 5% to 10%, such as 5%, 6%, 7%, 8%, 9% or 10%, etc., or other values ​​within the range of 5% to 10%. The above duty cycle can increase the effective discharge time and is conducive to the growth of film thickness; if the duty cycle is too high, it may cause overheating and deterioration of film quality.

[0057] The oxidation time of micro-arc oxidation can be 5min to 15min, such as 5min, 8min, 10min, 12min or 15min, etc., or other values ​​within the range of 5min to 15min. Within the above oxidation time range, as the oxidation time increases, the thickness of the micro-arc oxidation film gradually increases; but after exceeding 15min, the film growth rate decreases, and the film may even be degraded due to electrolyte corrosion.

[0058] After the micro-arc oxidation treatment is completed, the obtained micro-arc oxidation film layer is cleaned. For example, the magnesium alloy substrate with the micro-arc oxidation film layer can be placed in an ultrasonic cleaner for cleaning (eg, 5 minutes) to remove surface attachments.

[0059] As mentioned above, through micro-arc oxidation treatment, a corrosion-resistant oxide film can be formed on the surface of the magnesium alloy substrate, improving its corrosion resistance and slowing down the degradation rate. However, the micro-arc oxidation film usually has large pores and cracks, and the corrosive medium can easily penetrate into the surface of the magnesium alloy substrate through these defects, causing further corrosion of the substrate. Therefore, it is necessary to densify the micro-arc oxidation film by combining the post-treatment process to fill the pores and cracks, enhance the corrosion resistance of the coating, and maximize the protection needs of the magnesium alloy. The inventor proposes that if the surface of the micro-arc oxidation film is coated with a calcium-phosphorus coating, the calcium-phosphorus component in the calcium-phosphorus coating is similar to the human bone component, has good biocompatibility and bone inductivity, can improve the density of the coating and slow down the degradation rate of the magnesium alloy to a certain extent, but over time, the coating will gradually be eroded by the corrosive liquid, thereby losing its protective effect. Secondly, the porous structure may also cause the coating to have a weak bonding force with the magnesium alloy substrate, and it is easy to fall off or peel off. This will not only affect the protective effect of the coating, but also may cause damage to the surrounding tissues.

[0060] The present invention creatively proposes a solution of first subjecting the magnesium alloy to micro-arc oxidation treatment and then combining it with a polylactic acid glycolic acid-hydroxyapatite composite coating, which can effectively improve the above problems. The mechanism includes:

[0061] The degradation of magnesium alloy in the body occurs as follows: Mg+2H2O→Mg(OH)2+H2↑, which is alkaline and can easily cause local alkalization of tissues. If the pH is too high, it is not conducive to tissue healing. The degradation of polylactic acid-glycolic acid in the body occurs as follows: PLGA+H2O→lactic acid (C3H6O3)+glycolic acid (C2H4O3), which is acidic. When magnesium alloy and PLGA are degraded at the same time, the alkaline product (Mg(OH)2) and the acidic product (lactic acid and glycolic acid) neutralize each other, thereby effectively reducing the degree of alkalinity of local tissues, maintaining a more suitable biological environment, and promoting tissue repair and healing. Secondly, hydroxyapatite (HA) is a bioactive inorganic material that can release calcium ions (Ca 2+) during degradation. 2+ ) and phosphate ions (PO4 3- ), these ions play an important role in promoting bone tissue formation and regeneration.

[0062] The mixture of PLGA and HA materials can significantly enhance the bonding strength between HA and the micro-arc oxidation film on the surface of magnesium alloy. The PLGA matrix in the coating not only wraps and stabilizes the HA particles, but also improves its adhesion to the micro-arc oxidation film of magnesium alloy. The sustained release effect of PLGA allows the calcium ions (Ca) in HA to 2+ ) and phosphate ions (PO4 3- ) release is more uniform and lasting, further enhancing the effect of bone tissue regeneration. At the same time, it effectively improves the shedding or peeling phenomenon of HA in the body environment, ensuring the long-term stability of the coating.

[0063] In some optional embodiments, preparing the polylactic acid-glycolic acid-hydroxyapatite composite coating includes: immersing a magnesium alloy substrate having a micro-arc oxidation film layer in a mixed solution of polylactic acid-glycolic acid and hydroxyapatite, followed by vertical pulling and drying to form a polylactic acid-glycolic acid-hydroxyapatite composite coating on the surface of the micro-arc oxidation film layer.

[0064] The above-mentioned polylactic acid glycolic acid (PLGA) is a copolymer of lactic acid (PLA) and glycolic acid (PGA). Compared with PGA, the presence of side methyl groups in the PLA molecular chain makes it less hydrophilic and has a slower degradation rate; the hydrophilicity of the PGA material is better than that of PLA, but the degradation rate is too fast. Therefore, by regulating the copolymerization ratio of PLA and PGA, PLGA with different degradation rates can be obtained to meet the requirements of different tissue environments for material degradation performance. Among them, the copolymerization ratio of polylactic acid glycolic acid can be 50:50 to 85:15, such as 50:50, 75:25 or 85:15.

[0065] In some optional embodiments, the mixed solution includes a polymer solution formed by polylactic acid glycolic acid and a solvent and hydroxyapatite. The mixed solution can be prepared by first dissolving polylactic acid glycolic acid in a solvent, then adding hydroxyapatite, and stirring for 0.5h to 1h to uniformly disperse the hydroxyapatite.

[0066] Wherein, the solid-to-liquid ratio of polylactic acid glycolic acid to the solvent can be 5g:100mL to 10g:100mL; such as 5g:100mL, 5.5g:100mL, 6g:100mL, 6.5g:100mL, 7g:100mL, 7.5g:100mL, 8g:100mL, 8.5g:100mL, 9g:100mL, 9.5g:100mL or 10g:100mL, etc., and can also be other values ​​within the range of 5g:100mL to 10g:100mL. The solvent can illustratively be dichloromethane.

[0067] The mass ratio of hydroxyapatite to the polymer solution may be 5:100 to 20:100, such as 5:100, 8:100, 10:100, 12:100, 15:100, 18:100 or 20:100, or other values ​​within the range of 5:100 to 20:100.

[0068] If the content of polylactic acid glycolic acid in the mixed solution is too low, the final coating will be too thin, which is not conducive to the protection of the alloy; if the content of polylactic acid glycolic acid is too high, the solvent is not easy to volatilize, which is easy to cause residual solvent inside the coating, which is not conducive to the structural and performance stability of the coating. Similarly, if the content of hydroxyapatite in the mixed solution is too low, it is not conducive to promoting the attachment, growth and proliferation of bone cells; if the content of hydroxyapatite is too high, the viscosity of the solution increases, which is not conducive to the uniform distribution of hydroxyapatite particles.

[0069] In the present invention, when the polylactic acid glycolic acid-hydroxyapatite composite coating is prepared, it can be prepared by a pulling method or other conventional coating methods. The present invention preferably adopts a pulling method for preparation. Based on the surface tension of the liquid, the pulling method can obtain a very uniform coating, can avoid bubbles, and can prepare a thin film coating. By changing the pulling speed, the thickness of the film layer can also be controlled.

[0070] In some optional embodiments, the vertical pulling speed can be 0.5m / s to 3m / s, such as 0.5m / s, 1m / s, 1.5m / s, 2m / s, 2.5m / s or 3m / s, etc., or other values ​​within the range of 0.5m / s to 3m / s. The above coating times can be 1 time or multiple times, such as 2 times, 3 times, etc.

[0071] If the vertical pulling speed is too fast, the film-forming solution may be lost too quickly, the solution may not be fully spread, and an uneven liquid film may be formed.

[0072] Drying after vertical pulling can be carried out at 35°C to 45°C (such as 35°C, 40°C or 45°C, etc.) for 6h to 12h (such as 6h, 8h, 10h or 12h, etc.).

[0073] As mentioned above, the solution provided by the present invention can solve the problems existing in the existing medical magnesium alloy surface coating process, such as poor coating stability, local alkalization and complex preparation process. This solution can improve the comprehensive performance of magnesium alloy in the in vivo environment.

[0074] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0075] Example 1

[0076] The present embodiment provides a biomedical magnesium alloy, which includes a magnesium alloy substrate, a surface of the magnesium alloy substrate having a micro-arc oxidation film layer with a thickness of 6 μm, and a surface of the micro-arc oxidation film layer having a PLGA-HA composite coating with a thickness of 25 μm.

[0077] The preparation method of the biomedical magnesium alloy is as follows:

[0078] S1: Surface preparation

[0079] After cutting the magnesium alloy substrate into thin sheets of 20mm×20mm×1.5mm, it was polished in sequence using 400#, 800#, 1500# and 2000# sandpapers respectively until the surface was smooth without obvious scratches; the polished magnesium alloy substrate was then placed in an ultrasonic cleaner and cleaned with deionized water for 10 minutes; and a hole was drilled on the back of the magnesium alloy substrate for the aluminum wire to pass through and connect to the subsequent micro-arc oxidation power supply.

[0080] S2: Micro-arc oxidation treatment

[0081] S21: Prepare micro-arc oxidation electrolyte

[0082] NaOH, Na2SiO3 and EDTA-2Na are sequentially added into distilled water and stirred until the solution is completely transparent to obtain an electrolyte solution, wherein the concentration of NaOH is 10 g / L, the concentration of Na2SiO3 is 10 g / L, and the concentration of EDTA-2Na is 1 g / L.

[0083] S22: Micro-arc oxidation

[0084] The magnesium alloy substrate treated with S2 was connected to the anode of the micro-arc oxidation power supply and then immersed in the S21 electrolyte. The constant voltage mode was selected, and the voltage was set to 300 V, the frequency to 500 Hz, the duty cycle to 5%, and the oxidation time to 10 min.

[0085] S23: Post-processing

[0086] The sample obtained after the oxidation was completed was taken out and placed in an ultrasonic cleaner for cleaning for 5 minutes.

[0087] S3: Preparation of PLGA-HA composite coating

[0088] S31: Preparation of PLGA-HA mixed solution

[0089] Dissolve 0.5 g of PLGA (copolymerization ratio of 75:25) in 10 mL of dichloromethane and stir until completely dissolved to prepare a solution with a polymer mass to solvent volume ratio of 5%; add HA powder to the polymer solution at a mass fraction of 10% and stir for 0.5 h to ensure that the HA powder is evenly dispersed.

[0090] S32: Coating process

[0091] The magnesium alloy sample with the micro-arc oxidation film obtained in S23 was immersed in the PLGA-HA mixed solution of S31, and then the sample was vertically pulled at a speed of 1 cm / s; after the solvent evaporated, the coating was repeated twice.

[0092] S33: Drying

[0093] The coated sample was placed in a vacuum drying oven at 40°C and dried for 8 h to obtain a PLGA-HA composite coating with a uniform and dense surface.

[0094] Example 2

[0095] The difference between this embodiment and embodiment 1 is that the copolymerization ratio of PLGA used in S31 is 50:50.

[0096] Example 3

[0097] The difference between this embodiment and embodiment 1 is that the copolymerization ratio of PLGA used in S31 is 85:15.

[0098] Example 4

[0099] The present embodiment provides a biomedical magnesium alloy, which includes a magnesium alloy substrate, a surface of the magnesium alloy substrate having a micro-arc oxidation film layer with a thickness of 5 μm, and a surface of the micro-arc oxidation film layer having a PLGA-HA composite coating with a thickness of 20 μm.

[0100] The preparation method of the biomedical magnesium alloy is as follows:

[0101] S1: Surface preparation

[0102] After cutting the magnesium alloy substrate into thin sheets of 20mm×20mm×1.5mm, it was polished in sequence using 400#, 800#, 1500# and 2000# sandpapers respectively until the surface was smooth without obvious scratches; the polished magnesium alloy substrate was then placed in an ultrasonic cleaner and cleaned with deionized water for 5 minutes; and a hole was drilled on the back of the magnesium alloy substrate for the aluminum wire to pass through and connect to the subsequent micro-arc oxidation power supply.

[0103] S2: Micro-arc oxidation treatment

[0104] S21: Prepare micro-arc oxidation electrolyte

[0105] NaOH, Na2SiO3 and EDTA-2Na are sequentially added into distilled water and stirred until the solution is completely transparent to obtain an electrolyte solution, wherein the concentration of NaOH is 12 g / L, the concentration of Na2SiO3 is 5 g / L, and the concentration of EDTA-2Na is 3 g / L.

[0106] S22: Micro-arc oxidation

[0107] The magnesium alloy substrate treated with S2 was connected to the anode of the micro-arc oxidation power supply and then immersed in the S21 electrolyte. The constant voltage mode was selected, and the voltage was set to 250 V, the frequency to 1000 Hz, the duty cycle to 8%, and the oxidation time to 15 min.

[0108] S23: Post-processing

[0109] The sample obtained after the oxidation was completed was taken out and placed in an ultrasonic cleaner for cleaning for 5 minutes.

[0110] S3: Preparation of PLGA-HA composite coating

[0111] S31: Preparation of PLGA-HA mixed solution

[0112] Dissolve 0.8 g of PLGA (copolymerization ratio of 75:25) in 10 mL of dichloromethane and stir until completely dissolved to prepare a solution with a polymer mass to solvent volume ratio of 8%; add HA powder to the polymer solution at a mass fraction of 5% and stir for 0.5 h to ensure that the HA powder is evenly dispersed.

[0113] S32: Coating process

[0114] The magnesium alloy sample with the micro-arc oxidation film obtained in S23 was immersed in the PLGA-HA mixed solution of S31, and then the sample was vertically pulled at a speed of 0.5 cm / s; after the solvent evaporated, the coating was repeated twice.

[0115] S33: Drying

[0116] The coated sample was placed in a vacuum drying oven at 35°C and dried for 12 hours to obtain a PLGA-HA composite coating with a uniform and dense surface.

[0117] Example 5

[0118] The present embodiment provides a biomedical magnesium alloy, which includes a magnesium alloy substrate, a surface of the magnesium alloy substrate having a micro-arc oxidation film layer with a thickness of 10 μm, and a surface of the micro-arc oxidation film layer having a PLGA-HA composite coating with a thickness of 30 μm.

[0119] The preparation method of the biomedical magnesium alloy is as follows:

[0120] S1: Surface preparation

[0121] After cutting the magnesium alloy substrate into thin sheets of 20mm×20mm×1.5mm, it was polished in sequence using 400#, 800#, 1500# and 2000# sandpapers respectively until the surface was smooth without obvious scratches; the polished magnesium alloy substrate was then placed in an ultrasonic cleaner and cleaned with deionized water for 8 minutes; and a hole was drilled on the back of the magnesium alloy substrate for the aluminum wire to pass through and connect to the subsequent micro-arc oxidation power supply.

[0122] S2: Micro-arc oxidation treatment

[0123] S21: Prepare micro-arc oxidation electrolyte

[0124] KOH, Na3PO4 and glycerol were added to distilled water in sequence and stirred until the solution was completely transparent to obtain an electrolyte solution, wherein the concentration of KOH in the electrolyte solution was 15 g / L, the concentration of Na3PO4 in the electrolyte solution was 15 g / L, and the concentration of glycerol in the electrolyte solution was 10 g / L.

[0125] S22: Micro-arc oxidation

[0126] The magnesium alloy substrate treated with S2 was connected to the anode of the micro-arc oxidation power supply and then immersed in the S21 electrolyte. The constant voltage mode was selected, and the voltage was set to 500 V, the frequency to 1500 Hz, the duty cycle to 10%, and the oxidation time to 5 min.

[0127] S23: Post-processing

[0128] The sample obtained after the oxidation was completed was taken out and placed in an ultrasonic cleaner for cleaning for 5 minutes.

[0129] S3: Preparation of PLGA-HA composite coating

[0130] S31: Preparation of PLGA-HA mixed solution

[0131] Dissolve 1.0 g of PLGA (copolymerization ratio of 75:25) in 10 mL of dichloromethane and stir until completely dissolved to prepare a solution with a polymer mass to solvent volume ratio of 10%; add HA powder to the polymer solution at a mass fraction of 20% and stir for 1 hour to ensure that the HA powder is evenly dispersed.

[0132] S32: Coating process

[0133] The magnesium alloy sample with the micro-arc oxidation film obtained in S23 was immersed in the PLGA-HA mixed solution of S31, and then the sample was vertically pulled at a speed of 3 cm / s; after the solvent evaporated, the coating was repeated twice.

[0134] S33: Drying

[0135] The coated sample was placed in a vacuum drying oven at 45°C and dried for 6 hours to obtain a PLGA-HA composite coating with a uniform and dense surface.

[0136] Comparative Example 1

[0137] The difference between this comparative example and Example 1 is that only the micro-arc oxidation treatment is performed on the surface of the magnesium alloy, and the PLGA-HA composite coating is not prepared.

[0138] Test Example 1

[0139] Taking the biomedical magnesium alloys prepared in Examples 1 to 2 and Comparative Example 1 as examples, an in vitro degradation test was conducted.

[0140] Specifically, the above biomedical magnesium alloys were immersed in simulated body fluid (SBF) for 30 days, and the pH values ​​of the simulated body fluid at different days were recorded. The results are as follows: Figure 1 As shown, "micro-arc oxidation film" corresponds to Example 1, "micro-arc oxidation film + PLGA (50:50) / HA" corresponds to Example 2, and "micro-arc oxidation film + PLGA (75:25) / HA" corresponds to Example 1.

[0141] Depend on Figure 1 It can be seen that after the magnesium alloy in Comparative Example 1 was treated with micro-arc oxidation, in the simulated body fluid (SBF), the pH value of the simulated body fluid gradually increased with the extension of the in vitro degradation time. In contrast, when the PLGA-HA composite coating was introduced on the surface of the micro-arc oxidation film (such as Example 1 and Example 2), the pH value of the simulated body fluid was significantly reduced. In particular, when the PLGA copolymerization ratio was 75:25, after 30 days of in vitro degradation, the pH value of the simulated body fluid was still maintained at a low level, which shows that the PLGA-HA composite coating can effectively improve the local alkalinization effect caused by the degradation of the magnesium alloy.

[0142] Test Example 2

[0143] Taking the biomedical magnesium alloys prepared in Examples 1 to 2 and Comparative Example 1 as examples, a corrosion resistance test was conducted.

[0144] Specifically, the above biomedical magnesium alloys were immersed in simulated body fluid (SBF) for 30 days, and the corresponding potentiodynamic polarization curves after immersion for 1 day, 15 days and 30 days were recorded. The results are as follows: Figures 2 to 4 As shown. Among them, "micro-arc oxidation film" corresponds to Example 1, "micro-arc oxidation film + PLGA (50:50) / HA" corresponds to Example 2, and "micro-arc oxidation film + PLGA (75:25) / HA" corresponds to Example 1. The "E" in the horizontal axis represents (×10), such as 1E-11 represents 1×10 -11 .

[0145] Depend on Figures 2 to 4 It can be seen that compared with the single magnesium alloy micro-arc oxidation film (Comparative Example 1), the corrosion resistance of the magnesium alloy has been significantly improved after the PLGA-HA composite coating was introduced on its surface. Specifically, after the PLGA-HA composite coating was introduced, the self-corrosion potential increased significantly, indicating that the PLGA-HA composite coating effectively enhanced the corrosion resistance of the magnesium alloy, among which the self-corrosion potential of the composite coating sample with a PLGA copolymerization ratio of 75:25 was higher than that of the sample with a PLGA copolymerization ratio of 50:50; at the same time, the self-corrosion current density was significantly reduced, indicating that the PLGA-HA composite coating effectively reduced the speed of the corrosion reaction and further improved the corrosion resistance.

[0146] After immersion in simulated body fluid (SBF) for 1 day, 15 days and 30 days, the measured polarization curves all showed the same rule: the self-corrosion potential was micro-arc oxidation film + PLGA (75:25) / HA > micro-arc oxidation film + PLGA (50:50) / HA > single micro-arc oxidation film, and the self-corrosion current density was micro-arc oxidation film + PLGA (75:25) / HA < micro-arc oxidation film + PLGA (50:50) / HA < single micro-arc oxidation film.

[0147] The above results show that the introduction of PLGA-HA composite coating on the micro-arc oxidation film of magnesium alloy can significantly improve the corrosion resistance of the alloy, among which the coating with a PLGA copolymerization ratio of 75:25 shows better effect.

[0148] In summary, the present invention provides a good adhesion interface for the composite coating and enhances the corrosion resistance of the magnesium alloy substrate by using the micro-arc oxidation film as the surface modification base layer of the magnesium alloy. By introducing the PLGA-HA composite coating on the micro-arc oxidation film on the surface of the magnesium alloy, PLGA coats and stabilizes the HA particles, making their distribution more uniform, while improving the bonding strength between HA and the micro-arc oxidation film, reducing the peeling phenomenon of the coating, and ensuring the long-term stability of the coating. In addition, the composite coating further fills the pores and cracks of the micro-arc oxidation film, significantly improving the overall density and corrosion resistance, thereby effectively slowing down the degradation rate of the magnesium alloy.

[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A biomedical magnesium alloy, characterized in that: The biomedical magnesium alloy comprises a magnesium alloy substrate, the surface of the magnesium alloy substrate is provided with a micro-arc oxidation film layer, and the surface of the micro-arc oxidation film layer is provided with a polylactic acid glycolic acid-hydroxyapatite composite coating.

2. The biomedical magnesium alloy according to claim 1, characterized in that: The thickness of the micro-arc oxidation film layer is 5 μm to 10 μm; And / or, the thickness of the polylactic acid-glycolic acid-hydroxyapatite composite coating is 20 μm to 30 μm.

3. A method for preparing a biomedical magnesium alloy as claimed in claim 1 or 2, characterized in that: The following steps are involved: Performing micro-arc oxidation treatment on the magnesium alloy substrate to form a micro-arc oxidation film layer on the surface of the magnesium alloy substrate; A polylactic acid-glycolic acid-hydroxyapatite composite coating is prepared on the surface of the micro-arc oxidation film layer.

4. The preparation method according to claim 3, characterized in that: The micro-arc oxidation treatment includes: connecting the magnesium alloy substrate to a power source through a wire and performing electrical oxidation in an electrolyte.

5. The preparation method according to claim 4, characterized in that: The electrolyte comprises an alkali metal, an inorganic salt, an organic additive and water; The concentration of the alkali metal contained in the electrolyte is 10 g / L to 15 g / L, the concentration of the inorganic salt contained in the electrolyte is 5 g / L to 15 g / L, and the concentration of the organic additive contained in the electrolyte is 1 g / L to 10 g / L; Preferably, the alkali metal comprises at least one of KOH and NaOH; Preferably, the inorganic salt comprises at least one of Na2SiO3 and Na3PO4; Preferably, the organic additive includes at least one of EDTA-2Na and glycerol; wherein, when the organic additive contains EDTA-2Na, the concentration of EDTA-2Na in the electrolyte is 1g / L to 3g / L; when the organic additive contains glycerol, the concentration of glycerol in the electrolyte is 1g / L to 10g / L.

6. The preparation method according to claim 4 or 5, characterized in that: The voltage of the micro-arc oxidation treatment is 250V to 500V, the frequency of the micro-arc oxidation is 500Hz to 1500Hz, the duty cycle of the micro-arc oxidation is 5% to 10%, and the oxidation time of the micro-arc oxidation is 5min to 15min.

7. The preparation method according to claim 3, characterized in that: Before the micro-arc oxidation treatment, the method further includes performing surface pretreatment on the magnesium alloy substrate; And / or, before preparing the polylactic acid-glycolic acid-hydroxyapatite composite coating, the method further includes cleaning the micro-arc oxidation film layer.

8. The preparation method according to claim 3, characterized in that: The preparation of the polylactic acid glycolic acid-hydroxyapatite composite coating comprises: immersing the magnesium alloy substrate having the micro-arc oxidation film layer into a mixed solution of polylactic acid glycolic acid and hydroxyapatite, then vertically pulling and drying to form the polylactic acid glycolic acid-hydroxyapatite composite coating on the surface of the micro-arc oxidation film layer.

9. The preparation method according to claim 8, characterized in that: The mixed solution includes a polymer solution formed by polylactic acid-glycolic acid and a solvent and hydroxyapatite; wherein the solid-liquid ratio of polylactic acid-glycolic acid to the solvent is 5g:100mL to 10g:100mL; the mass ratio of the hydroxyapatite to the polymer solution is 5:100 to 20:100; And / or, the copolymerization ratio of the polylactic acid / glycolic acid is 50:50 to 85:

15.

10. The preparation method according to claim 8, characterized in that: The vertical pulling speed is 0.5m / s~3m / s; And / or, drying is performed at 35° C. to 45° C. for 6 h to 12 h.

Citation Information

Patent Citations

  • Preparation method of magnesium alloy surface micro-arc oxidation-electrophoresis composite coating

    CN104611699A

Cited By

  • High-corrosion-resistance biomedical degradable magnesium-based composite material and solid-phase additive preparation method thereof

    CN120285305A

  • High-corrosion-resistance biomedically degradable magnesium-based composite material and solid-phase additive manufacturing method thereof

    CN120285305B

  • A porous magnesium alloy bone nail for promoting bone regeneration and a surface treatment method thereof

    CN122582357A